Joelle's secret [large type] - Morris, Gilbert (Thorndike Press large print Christian historical fiction, 2009)
To escape the unwelcome advances of her stepfather, who is declared her guardian after mother's death, seventeen-year-old Joelle cuts her hair, poses as a young man, and joins a wagon train to gold-rich California.